THE PECULIARITIES OF THE CENTRAL HEMODYNAMICSFORMATION AMONG THE CHILDREN IN LONG-TERM REMISSION OF ACUTE LYMPHOBLASTIC LEUKEMIA - E. D. Teplyakova; A. A. Savisko (Медицинский вестник Юга России, 2013)
Purpose: To identify the peculiarities of the central hemodynamics formation among the children in long-term remission of acute lymphoblastic leukemia.Materials and Methods: The monitored group consisted of 22 children having been in long-term remission of acute lymphoblastic leukemia for more than 5 years. All the children had previously been treated according to the standard and intermediate risk groups of the ALL-MB-2002protocol. The control group included 81 children belonging to the first and second health groups. All the children had gone through a complex medical examination including electrocardiography, cardiointervalography, Doppler echocardiography.Results: Cardiac syndrome is significantly more frequently registered among the children in long-term remission of acutelymphoblastic leukemia. At the same time authentic differences in the incidence of repolarization violations were detected among the patients in long-term remission of acute lymphoblasticleukemia. Early signs of diastolic myocardial dysfunction were also revealed among the patients with acute lymphoblastic leukemia despite the absence of systolic function changes and hyperkinetic type of blood circulation was significantly more often formed. In assessing the vegetative function the prevalence of the original sympathicotony and asympathicotonic vegetative reactivity was established.